Transplantation of Lymphocytes Co-Cultured with Human Cord Blood-Derived Multipotent Stem Cells Attenuates Inflammasome Activity in Ischemic Stroke - Zhao Y (Dove Medical Press, 2019)
Yanxin Zhao,* Tianrui Zhu,* Heng Li, Jing Zhao, Xiaohong Li Department of Neurology, Jinan Central Hospital Affiliated to Shandong University, Jinan, Shandong 250013, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaohong LiDepartment of Neurology, Jinan Central Hospital Affiliated to Shandong University, No. 105 Jiefang Road, Jinan, Shandong 250013, People’s Republic of ChinaTel +86-0531-68623309Fax +86-0531-85695219Email xiaohong-li@sdu.edu.cnBackground: Manipulating the immune inflammatory response after cerebral ischemia has been a novel therapeutic strategy for ischemic stroke. This study attempted to investigate the effects of the transplantation of lymphocytes co-cultured with human cord blood-derived multipotent stem cells (HCB-SCs) on the inflammatory response in transient middle cerebral occlusion (tMCAO) rats.Methods: The tMCAO rats were subjected to the transplantation of lymphocytes co-cultured with HCB-SCs through tail vein injection. Infarct size and neurological deﬁcits were measured at 48 hrs after stroke. Neurological deﬁcits were assessed using Bederson’s scoring system and tape removal test. Blood T cell flow cytometry was performed to measure the differentiation of regulatory T cells (Tregs). Western blot was used to detect the protein levels of inflammation-related molecules, apoptosis-related molecule, and signaling molecules in ischemic brain. TUNEL staining was performed to analyze cell apoptosis in ischemic cerebral cortex.Results: The transplantation of lymphocytes co-cultured with HCB-SCs significantly improved the neurological defects, reduced ischemic brain damage, and increased the proportion of peripheral CD4+CD25+Foxp3+ Tregs. Meanwhile, the transplantation of co-cultured cells decreased the expression of NLRP3 inflammasome and associated factors, such as caspase-1 and IL-1β, and inhibited the activation of NF-κB, ERK and caspase-3 in ischemic brain. The co-cultured cells significantly decreased the number of tMCAO-induced cell apoptosis.Conclusion: Lymphocytes co-cultured with HCB-SCs exhibit a neuroprotective effect after ischemic stroke by promoting Tregs differentiation and suppressing NLRP3 inflammasome activation and neuron apoptosis, and might be a promising therapeutic strategy for ischemic stroke.Keywords: ischemic stroke, inflammation, cord blood-derived multipotent stem cells, regulatory T-cells, inflammasomes